COMING TO TERMS AS A CHRISTIAN HISTORIAN WITH F. H. BRADLEY. - Noll, Mark A. (Fides et historia, 2011)
An essay is presented which examines philosopher F. H. Bradley's writings on the role of historians' religious beliefs in their work. Particular focus is given to Bradley's theories on the critical practice of history and the relationship between history and science. According to the author, the Christian experience of the world as a place in which God is both transcendant and immanent does not conflict with a view of history rooted in cause, effect, and the natural world.